Vitrectomy and gas for inferior break retinal detachments: are the results comparable to vitrectomy, gas, and scleral buckle?. Issue 11 (15th October 2004) - Wickham, L; Connor, M; Aylward, G W
Abstract : Aims: To compare the success rates of vitrectomy and gas with vitrectomy, gas, and buckle in the treatment of inferior break retinal detachments. Methods: A retrospective case note review of 86 patients who presented with inferior break retinal detachments was carried out. An inferior break was defined as a horseshoe tear present between 4 and 8 o'clock. Patients were analysed in two groups; group A consisted of 41 patients who underwent a vitrectomy and gas, group B consisted of 45 patients who underwent a vitrectomy, gas, and scleral buckle. The features of the retinal detachment, peroperative and postoperative complications, and outcomes of treatment were recorded for each patient. Results: The primary anatomical success rate at 3 months was 89% in group A versus 73% in group B (p = 0.11). There was no statistical difference in the complication rate between the two groups (p = 0.819). The most common cause of treatment failure was proliferative vitreoretinopathy, 20% (n = 9) in group B compared with 5% (n = 2) in group A and this reached statistical significance (p = 0.0159). There was a higher rate of epiretinal membrane development in group B (p = 0.0004). The final attachment rate was not statistically different between the two groups, 95% (39) in group A and 93% (42) in group B (p = 1.0). Conclusion: Vitrectomy and gas without the application of a scleral buckle may be used to safely treat inferior break retinal detachments. It may be used as an alternative to vitrectomy, gas, and buckle which has an increased risk of choroidal haemorrhage, requires a longer operating time, and has all the associated complications of a scleral buckle.